Identifikasi Senyawa Fitokimia dan Uji Aktivitas Antioksidan pada Cascara (Coffea arabica L.) - Sasadara, Maria Malida Vernandes; Cahyaningsih, Erna; Yuda, Putu Era Sandhi Kusuma; Handani, Dewa Ayu Sri; Dewi, Ni Luh Kade Arman Anita; Megawati, Fitria; Tirtayasa, Gede Agus Ari (Usadha, 2025)
Cascara refers to the dried husk of coffee cherries. It has garnered significant attention in recent research due to its phytochemical composition and potential health benefits. Several studies have highlighted the presence of bioactive compounds and the antioxidant activity exhibited by cascara. This study aims to investigate the phytochemical content and antioxidant potential of cascara. The cascara was extracted using the maceration method with 96% ethanol, followed by phytochemical screening for alkaloids, flavonoids, tannins, saponins, terpenoids, steroids, and quinones using standard color reactions in test tubes. Antioxidant activity was assessed via the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, with ascorbic acid as a reference compound. The phytochemical profile of the extract was identified using gas chromatography-mass spectrometry (GC-MS). The findings indicated that cascara contains alkaloids, flavonoids, tannins, saponins, and triterpenoids. GC-MS analysis identified caffeine, hexadecanoic acid (methyl ester), and hexadecanoic acid (ethyl ester) as the predominant compounds in cascara. The antioxidant activity test using the DPPH method demonstrated that the ethanol extract of cascara possesses moderate antioxidant potential, with an average IC50 value of 108.49 ± 1.28 ppm. Ascorbic acid, the reference compound used in this study, yielded an IC50 of 2.53 ppm, categorized as very strong. This research underscores cascara’s potential as a valuable source of antioxidants with significant health benefits, influenced by geographic factors affecting its bioactive compound profile. Consequently, cascara holds promise for further development as a raw material for functional health-promoting products.